PENGARUH FINANCIAL STABILITY, EXTERNAL PRESSURE, FINANCIAL TARGETS, INEFFECTIVE MONITORING, OPINI AUDIT, DAN CHANGE IN DIRECTOR TERHADAP FINANCIAL STATEMENT FRAUD DALAM PERSPEKTIF FRAUD DIAMOND (Studi Empiris pada Perusahaan LQ-45 yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2016) - Evi Anita Susanti. S; R. Adri Satriawan Surya; Arumega Zarefar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to obtain empirical evidence about the effectiveness of the fraud diamond in detecting financial statement fraud. The element of the fraud diamond that is used as independent variables is a pressure with proxy financial stability (ACHANGE), external pressure (LEV), and financial targets (ROA), opportunity with proxy ineffective monitoring (BDOUT), rationalization with proxy the audit opinion (AUDREP), and capability with proxy change in director (DCHANGE). In this research uses a proxy earnings management with discretionary accruals as the dependent variable. The population of this research is the LQ-45 companies listed in Indonesia Stock Exchange in 2011-2016. Total sample of this research is 20 companies with six years observation.Data analysis was performed with the classical assumption and hypothesis testing using multiple linear regressionmethod by SPSS version 16.00. The results indicates that the financial stability (ACHANGE) and financial targets (ROA) influence the financial statement fraud. Meanwhile, the external pressure (LEV), ineffective monitoring (BDOUT), audit opinion (AUDREP), and change in director (DCHANGE) has no significant impact on financial statement fraud.The influence of the independent variables to describe the dependent variable is 33,1%, while the remaining 66,9% is influenced by other variables.Keywords : Financial Statement Fraud, Earnings Management, Fraud Diamond.